Accuracy of Le Fort I osteotomy in bimaxillary splint-based orthognathic surgery: focus on posterior maxillary movements. Issue 11 (November 2018) - Govaerts, D.; Shaheen, E.; Coopman, R.; De Mol, A.; Sun, Y.; Politis, C.
Abstract: This retrospective study was performed to verify the accuracy of horizontal and vertical repositioning of the maxilla in bimaxillary osteotomy with a focus on posterior vertical displacement. Data from 39 orthognathic patients undergoing bimaxillary surgery including a one-piece Le Fort I osteotomy with pitch rotation and advancement at the University Hospitals of Leuven (Belgium), between January 2015 and April 2016, were included in the study. Preoperative and 1-week postoperative lateral cephalograms were digitized and imported into cephalometric software. Horizontal and vertical measurements of dental landmarks were used to assess the accuracy of maxillary repositioning, and errors were reported in terms of the mean and absolute mean. The horizontal advancements were randomly under- and over-corrected an average of 1.4 mm ± 1.2 mm. Vertical repositioning of the anterior maxilla followed the planning. A tendency for under-correction was found for posterior vertical intrusion of the maxilla. The same tendency towards under-correction of posterior maxillary inferior repositioning was detected when planned movements were greater than 3 mm. For all studied groups, no significant difference was found between the planning and the results achieved, validating the use of intermediate splints.